Dari Penciptaan hingga Pemuridan: Fondasi Biblika-Teologis bagi Pemulihan Kesetaraan Gender - Marde Christian Stenly Mawikere; Sudiria Hura (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. Gender inequality is a complex issue involving biological, cultural, social, and theological dimensions. This study examines the biblical-theological foundation for restoring gender equality based on the continuity of the narrative of creation, the fall, and redemption in Christ. Using a literature study method, an analysis was conducted of biblical texts, systematic theology literature, and contemporary socio-cultural studies. The result of the study indicate that humans were created equal as the imago Dei, but the fall brought relational distortions that gave rise to gender injustice. True restoration is only possible through Christ's redemption, which opens up space for holistic discipleship as an ethical and transformative strategy.Abstrak. Ketidaksetaraan gender merupakan isu kompleks yang melibatkan dimensi biologis, kultural, sosial, dan teologis. Penelitian ini menelaah fondasi biblika-teologis bagi pemulihan kesetaraan gender berdasarkan kesinambungan narasi penciptaan, kejatuhan, dan penebusan dalam Kristus. Dengan metode studi kepustakaan, analisis dilakukan terhadap teks Alkitab, literatur teologi sistematik, serta kajian sosial-kultural kontemporer. Hasil kajian menunjukkan bahwa manusia diciptakan setara sebagai imago Dei, tetapi kejatuhan membawa distorsi relasional yang melahirkan ketidakadilan gender. Pemulihan hakiki hanya dimungkinkan melalui penebusan Kristus, yang membuka ruang bagi pemuridan holistik sebagai strategi etis dan transformatif.